The Active Self in Contemporary Saudi Visual Art)The Dialectic of the Self and Cultural Transformation( (Al-Academy, 2025)
The concept of the active ego in contemporary Saudi art addresses the role of Saudi artists in shaping the local and global art scene, such that art reflects the artist's personal identity and their interaction with the social, cultural, and technical context of the Kingdom. The active ego emerges as a philosophical perspective that focuses on the Saudi artist's ability to reproduce local symbols and images within a dialectical framework that interacts with the realities of globalization and cultural openness. This is how the active ego is realized in contemporary Saudi visual art. The research adopted a descriptive and analytical approach and reached several conclusions, including that the active ego is not an expressive self, but rather a meaning-producing self within the expressive context of contemporary Saudi art. The relationship between the artistic self and cultural transformation is a dynamic, dialectical one, where the active ego appears in multiple forms in contemporary Saudi art, but they share critical awareness, cultural responsibility, and existential boldness. The research recommends conducting further studies on the active ego in light of the artistic expression of Saudi culture and global transformations, and holding workshops and seminars to deepen the understanding of the creative self among Saudi artists